Abū Isḥāq al-Shīrāzī’s Model of Behaviour Modification: An Inductive Study on his Book “Al-Ṭib Al-Rūḥānī” - Ibrahim Bouzidani; Mutiu Olagoke Salami (Darulfunun Ilahiyat)
This study examines the behavioural modification model of Abū Isḥāq Ibrāhīm ibn ‛Alī al-Shīrāzī. The model is explained in his book titled: “Al-Ṭib Al-Rrūḥānī” (The Spiritual Medicine). The proposed framework is developed by adopting treatment methodologies in organic medicine to behaviour modification. Thus, the model was developed to have four phases: identification of the disease, symptom, cause, and treatment. The researchers targeted two objectives; first, to investigate the theoretical basis of al-Shīrāzī’s model, and secondly, to find ways to enrich the scientific domain by introducing al-Shīrāzī’s contributions to the field of psychology and behavioural modification. In summary, this review study adopted the Inductive Content Analysis, which is based on the description and interpretation of textual data and the interpretation process aimed at developing knowledge and understanding of the phenomenon under study. Some notable behavioural theories were selected based on their change and modification paradigms, which were compared with those of al-Shirazi. This is intended to extrapolate the intellectual legacy of Abū Isḥāq al-Shīrāzī, may God Almighty have mercy on him.